Low Birth Weight and Dental Fluorosis: - Jayanth V. Kumar, DDS, MPH; Philip A. Swango, DDS, MPH; Pandy N. Opima, DDS, MPH; (Blackwell Synergy, 2000)
The association between low birth weight and dental fluorosis was explored in a cross-sectional study to explain the higher prevalence of dental fluorosis among African-American children.